“Why Santa but not witches?”: Parents' reasoning behind encouraging and discouraging fantasy beliefs in children - Yoo, Seung Heon; Jiang, Matthew J.; Rosengren, Karl S. (Frontiers in Developmental Psychology, 2025)
IntroductionDuring the preschool years, children begin to distinguish fantasy and reality. In the United States, this is often the time parents encourage belief in certain fantasy figures (e.g., Santa Claus) while discouraging belief in others (e.g., witches). Although prior research primarily focusing on Santa Claus provided why parents support that belief, less is known about their support of childhood fantasy beliefs more broadly. Moreover, the role of child and parental factors in shaping parents' decisions to support such beliefs has not been investigated in detail. To address these gaps, we conducted two studies. We also examined whether parental support, as well as parents' own and their children's beliefs in fantasy figures, have changed over the past 30 years.MethodsWe recruited parents of children aged 3–8 years living in the United States for both studies. Study 1 (n = 39) was an in-person interview study in which parents reported their own and their child's fantasy beliefs, their views on childhood fantasy beliefs, and their motivations for supporting fantasy beliefs. Study 2 (n = 486) was an online survey adapted from Study 1, designed to examine how individual factors relate to parental support of fantasy beliefs.ResultsOverall, the results suggest that parents support childhood fantasy beliefs to promote their child's wellbeing by creating an exciting childhood, fostering cultural understanding, and protecting children from negative emotions (e.g., fear). These findings were consistent across the two studies, although some variations were observed in parental reports of their own and their child's beliefs and their support when compared with a study from the 1990s. Parents' decisions to support fantasy beliefs were associated with their attitudes toward fantasy beliefs, their religiosity, and their child's age.DiscussionParents viewed fantasy beliefs as a normal part of childhood and promoted them for their perceived benefits to the child. However, the current findings suggest that parents navigate supporting these beliefs in complex and adaptive ways, balancing cultural norms, personal experiences, children's developmental considerations, and religious values, to determine which beliefs they encourage or discourage in their children's imaginative lives. Differences observed over the past 30 years in children's beliefs and parental support are discussed in relation to broader cultural changes.